Analisis Kinerja Anggaran Pemerintah Provinsi Sumatera Selatan Dengan Pendekatan Konsep Value For Money - Periansya Periansya; Dendy Pratama; Rosi Armaini (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2021)
This research is intended as an effort to analyze the budget performance of Regional Apparatus Organizations in South Sumatra Province with a value for money concept approach. This study consisted of the dependent variable, namely the performance of the regional apparatus organization budget, while the independent variable consisted of transparency, accountability, and supervision. The data used in this research is the result of distributing questionnaires to selected respondents in 21 Regional Apparatus Organizations. The sample selection technique used purposive sampling, while the data analysis technique used multiple linear regression. The results of the analysis and discussion of hypothesis testing show that partially transparency, accountability, and supervision have a positive and significant effect on-budget performance, including simultaneously also showing a positive and significant effect on-budget performance, but it is necessary to increase budget performance, this shows that the R2 value is 0.446. or 44.6%.